Pengaruh Operating Leverage, NDTS, Struktur Aktiva, dan Growth Opportunity terhadap Struktur Modal - Liestyasih, Luh Putu Erma; Yadnya, I Putu (E-Jurnal Manajemen, 2015)
Capital structure illustrates the combination of debt dan equity in the company’s long term financial structure. The Factors that can affect the capital structure must be observed by the manager in determining the optimal capital structure. This study was purpose to determine the effect of operating leverage, non-debt tax shield, assets structure and sales growth opportunity to capital structure. Sample in this study is 11 companies with nonprobability purposive sampling as sampling method . Research with multiple linear regression analysis found that there is a significant positive relation between operating leverage and capital structure. Assets structure showed the significant negative relation on capital structure, non-debt tax shield and sales growth opportunity showed no significant effect on capital structure.
Keywords: capital structure, operating leverage, non-debt tax shield, assets structure, sales growth opportunity